Group Exhibition-IKB International Klein’s Blue, Ist Volos Summer Exhibition - Antoniou, Klitsa (My University, 2026)
IKB International Klein’s Blue, Ist Volos Summer Exhibition, Old Volos Nursing Home, Volos Greece. Curated by Chrysa Drantaki